Pengaruh Perubahan Status Gizi Pasien Dewasa terhadap Lama Rawat Inap dan Biaya Rumah Sakit - R Dwi Budiningsari (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2004)
Background: The decline in nutritional status of hospitalized patients was reported to be assossiated with longer length of stay and higher hospital charges. However, the effect of changes in nutritional status on hospital outcomes in Indonesia is still unknown.Objective: To determine the effect of changes in nutritional status on length of stay and hospital charge among adult hospitalized patients.Method: A total subjects of 262 adult patients who were admitted to internal and neurology departments of Dr. Sardjito, Dr.M.Jamil, and Sanglah hospitals were included in this study. Nutritional status of each patient was assessed using Subjective Global Assessment (SGA) method. Information on length of stay and hospital charge was collected based on medical records.Results: Subjects with nutritional status declined from normally to moderately, normally to severely, and moderately to severely malnourished were 6,3 (OR=6.32, 95% CI=1,3-29,8); 11,9 (OR=11.94, 95% CI=1,02-139,1); and 6,90 (OR=6.9, 95%CI=1,5-32,0 )times more likely to stay longer than those with nutritional status stayed normal during hospitalitation. They also had 3,3; unlimited; and 1,76 times risk on higher hospital charges than reference group (95% CI=1,123-9,529; unlimited; and 0,590-5,245).Conclusions: The declines of nutritional status from normally to moderately, normally to severely, and moderately to severely malnourished in hospitalized patients influenced to longer length of stay. Normally to moderately and normally to severely malnourished in hospitalized patients influenced to higher hospital charges.